The drama prior to and including Shakespeare - Wiest, Amelia Jennie (My University, 1904)
Introduction: The drama is a presentation of an action or of a series of combined actions by means of speech and gesture. Its subject matter is the action and reaction of the human will and is treated in relation to the causes and effects of events. The drama was conceived in a desire to vividly express thought and feeling. Furhermore, it is to society that man is indebted for his ability to express his ideas and emotions by means of language and gestures or through a combination of both. Moreover, these expressions vary as the occasion in joyous or sad and they are acquired mainly by imitation, a quality which is instinctive in man. This quality is especially noticeable in children who take great delight in adorning themselves to imitate their elders; for instance, who has not seen the little girl decked in her mother’s wardrobe playing “lady”? This assumption of a real or of a fanciful character is the first step in the drama, but not until the imitation is put into action is the drama itself reached. The classic departments of the drama are “tragedy” and “comedy” terms handed down to us from the Greeks.
Citation: Wiest, Amelia Jennie. The drama prior to and including Shakespeare. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Shakespeare; Dramas; History of Dramas; Types of Dramas; Performing Arts; Theses; Manuscripts (documents)